2012
DOI: 10.1002/pc.22201
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on reprocessing of extruded wood flour/HDPE composites

Abstract: This article presents an experimental study on the change in the properties of wood–plastic composites (WPCs) when reprocessed. The degree of properties degradation upon reprocessing, for recycling purpose, can be considered as a key factor to choose an alternative against discarding into the environment. A material which retains its properties when recycled, or at least exhibits insignificant reduction in its properties, is favorable in environmental point of view. To investigate the reprocessing effect on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 44 publications
5
46
0
Order By: Relevance
“…The polymer–filler interfacial interaction and its quality are the most important factors that influence the mechanical properties of the composite. A good bond between wood and polymer improves the stress transfer and as a result the mechanical properties, as reported by Shahi et al, Tasdemir et al, and Godard et al .…”
Section: Discussionsupporting
confidence: 64%
“…The polymer–filler interfacial interaction and its quality are the most important factors that influence the mechanical properties of the composite. A good bond between wood and polymer improves the stress transfer and as a result the mechanical properties, as reported by Shahi et al, Tasdemir et al, and Godard et al .…”
Section: Discussionsupporting
confidence: 64%
“…However, they obtained from 4% to 8% lower crystallinity for heat‐treated alder wood. Other studies found lower crystallinity for different types of HDPE filler . For example, Cui et al .…”
Section: Resultsmentioning
confidence: 92%
“…Wood flour composites display similar tensile strength properties to the laboratory scale TMP composites, but wood flour composites reveal higher MOE. An explanation for this phenomenon may be, that smaller particles with lower aspect ratio disperse more easily in the polymer matrix resulting in additional homogeneity and therefore stiffer composites . Furthermore, it is assumed here, that twin‐screw extruders have a larger free volume within the mixing barrel compared to laboratory scale compounding technologies.…”
Section: Methodsmentioning
confidence: 99%